The Effect of Work Motivation On The Performance of Employees of The Regional Public Service Agency For The Drinking Water Supply System of The Public Works And Spatial Planning Service of East Nusa Tenggara Province - Anggriany Nitte, Yullen; C. Neolaka, M. N.B.; Salim Adang Djaha, Ajis; Ugobueze, Ngozi (International Journal of Educational Research & Social Sciences, 2023)
Low employee performance and its relation with extrinsic and extrinsic work motivation have been the focus of this study. The study examines how extrinsic and intrinsic motivation partially and simultaneously affect the performance of employees at the Regional Public Service Agency for the Drinking Water Supply System of the Public Works and Spatial Planning Service (Badan Layanan Umum Daerah Sistem Penyediaan Air Minum Dinas Pekerjaan Umum dan Penataan Ruang - BLUD SPAM of DPUPR) of East Nusa Tenggara Province. This study was quantitative, with a cross-sectional approach from September to November 2020. The population was 38 employees, and the sample consisted of 33 people determined purposively by considering their willingness to be respondents. We used a questionnaire as the instrument, and data were analyzed using descriptive statistical analysis and simple and multiple linear regression analysis. The results show that extrinsic motivation, including incentives, working conditions, work relationships between leaders and staff, and job security, partially affects employee performance. Intrinsic motivation, including the work itself, responsibility, work knowledge, and work performance, partially influences employee performance. Extrinsic and intrinsic motivation simultaneously influence employee performance. It can be concluded that there is a positive and significant influence between extrinsic and intrinsic motivation partially and simultaneously on the performance of employees of the Regional Public Service Agency for the Drinking Water Supply System of the Public Works and Spatial Planning Service (Badan Layanan Umum Daerah Sistem Penyediaan Air Minum Dinas Pekerjaan Umum dan Penataan Ruang - BLUD SPAM of DPUPR) of East Nusa Tenggara Province.